Paleomagnetism of the Mudcracked formation of the Precambrian Little Dal Group, Mackenzie Mountains, Northwest Territories, Canada - Park, John K. (Canadian Journal of Earth Sciences, 1984)
A previous study detailed the paleomagnetism of red limestones of the Little Dal Group Basinal assemblage, but failed to prove whether the magnetization carried by the red pigment was prefolding. The present study on "red" sandstones of the immediately underlying Mudcracked formation, using acid leaching at three sites, revealed a paleomagnetic direction B in the pigment (266°, −17°; seven samples; k = 28; α 95 = 12°), which closely agrees with the probable pigment direction of the Basinal assemblage (273°, −09°; 12 sites; α 95 = 11°). Since a fold test of the B sample directions is significant at the 95% probability level, I suggest that the pigment in both units is prefolding (pre-Paleocene at latest).